2016
DOI: 10.1371/journal.pone.0166519
|View full text |Cite
|
Sign up to set email alerts
|

Extended-Spectrum beta (β)-Lactamases and Antibiogram in Enterobacteriaceae from Clinical and Drinking Water Sources from Bahir Dar City, Ethiopia

Abstract: BackgroundThe spread of Extended-Spectrum beta (β)-Lactamases (ESBL)-producing Enterobacteriaceae has become a serious global problem. ESBL-producing Enterobacteriaceae vary based on differences in antibiotic use, nature of patients and hospital settings. This study was aimed at determining ESBL and antibiogram in Enterobacteriaceae isolates from clinical and drinking water sources in Bahir Dar City, Northwest Ethiopia.MethodsEnterobacteriaceae species were isolated from clinical materials and tap water using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
29
6
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 20 publications
16
29
6
2
Order By: Relevance
“…In contrast the Cephalosporins (Ampicillin/ Cloxacillin, Amoxicillin/ Clavulanate, and Cefuroxime axetil) with the exception of Ceftriaxone, Imipenem and Cefoxitin, were not as effective, especially against the gram negative isolates, these results were consistent with the findings of other researchers [14,15]. This could be as a result of a growing resistance to the β-lactams component of these antibiotics, by β--lactamase producing bacteria such as Staphylococcus aureus [27], suggesting the development of Methicillin Resistant Staphylococcus aureus (MRSA); and especially extended-spectrum β-lactamases (ESBLs) producers such as Klebsiella pneumoniae, Klebsiella oxytoca, Escherichia coli and Proteus mirabilis, which possess grave consequences to public health [28,12,29].…”
Section: Figure 1: Comparative Analysis On the Level Of Bacterial Consupporting
confidence: 88%
“…In contrast the Cephalosporins (Ampicillin/ Cloxacillin, Amoxicillin/ Clavulanate, and Cefuroxime axetil) with the exception of Ceftriaxone, Imipenem and Cefoxitin, were not as effective, especially against the gram negative isolates, these results were consistent with the findings of other researchers [14,15]. This could be as a result of a growing resistance to the β-lactams component of these antibiotics, by β--lactamase producing bacteria such as Staphylococcus aureus [27], suggesting the development of Methicillin Resistant Staphylococcus aureus (MRSA); and especially extended-spectrum β-lactamases (ESBLs) producers such as Klebsiella pneumoniae, Klebsiella oxytoca, Escherichia coli and Proteus mirabilis, which possess grave consequences to public health [28,12,29].…”
Section: Figure 1: Comparative Analysis On the Level Of Bacterial Consupporting
confidence: 88%
“…There were also similar findings from studies conducted in Gondar (68.0%) [25], Dessie (74.6%) [26], Debre Markos: (72.2%) [21] and Nepal (64.0%) [27]. However, our result was lower than studies done in Sierra Leone (85.7 %) [24], Gondar (87.4%) [16], Bahir Dar (93.1%) [28], Nepal (96.8%) [29].The difference in magnitude of MDR isolates might be due to patient condition, definition for MDR and empirical treatment trend. In addition, our result was higher when compared to a previous study done in Jimma (59.3%) [30], Nepal (54.2%) [27], another study in Nepal by Lamichhane et al [31] reported (33.14%).…”
Section: Multi Drug Resistance Pattern Of Gram Negative Bacillisupporting
confidence: 87%
“…However, the magnitude of ESBLs production among GNB in our study was lower than studies done in Addis Ababa 57.7% [36], Bahir Dar 57.6% [28], North West Nigeria 58.0% [37], Southwestern Uganda 89% [38] and Southeast Iran 53.8% [23]. This wide variation might be due to differences in study population, type of specimen, sample size, the extent of antibiotic use and mainly the methodology used.…”
Section: Magnitude Of Esbls Producing Gram Negative Bacillicontrasting
confidence: 62%
“…It has been assumed that the environment such as drinking water is one of the potential sources of ESBL producers in developing countries where no reliable waterworks and sewage systems have been equipped [155][156][157][158] . In those countries, various antimicrobial-resistant bacteria including ESBL producers have been recovered even from drinking water 155,157,159) and vegetables 160) . The origins of ESBL producers in drinking water were speculated to be the sewage or drainage from human and livestock [161][162][163][164][165] .…”
Section: Potential Source Of Esbl Genes Found In Healthy People 6-1 Pmentioning
confidence: 99%